Contemporary Perspectives On The Impact Of Enzymatic Dysfunction In The Pathogenesis Of Female Infertility And Innovative Approaches To Its Treatment (Literature Review) (Texas Journal of Medical Science, 2024)
To conduct a comprehensive analysis of modern aspects of enzymatic dysfunction in female infertility and to explore innovative methods for its correction